Fistula as a Public Health challenge in Pakistan - Noushad, Shamoon; Syed, Shershah; Ahmed, Sadaf (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To explore the impact of obstetric fistula in the county and to propose effective public health interventions that can help to prevent the condition with a long-term goal of eradicating the condition. Methods: The survey and analysis included secondary data addressing women's experiences of fistula; dynamics and limitationsdetermining women's access to in healthcare facilities for fistula management; and restraintsof health professional as well as health inequities. Results: It was assessed that recently, many hospitals and organizations in the country go on board on intercessions to address the impact of the illness, however, much importance is on pinpointing and discussing the existing cases rather than focusing on public health interventions that can help to prevent and eventually eradicate the condition in Pakistan.